2011
DOI: 10.4049/jimmunol.1001753
|View full text |Cite
|
Sign up to set email alerts
|

FcR-Independent Effects of IgE and IgG Autoantibodies in Bullous Pemphigoid

Abstract: Bullous pemphigoid (BP) is a subepidermal blistering disease characterized by IgE and IgG class autoantibodies specific for 180-kDa BP Ag 2 (BP180), a protein involved in cell-substrate attachment. Although some direct effects of BP IgG have been observed on keratinocytes, no study to date has examined direct effects of BP IgE. In this study, we use primary cultures of human keratinocytes to demonstrate Ag-specific binding and internalization of BP IgE. Moreover, when BP IgE and BP IgG were compared, both isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
69
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 52 publications
7
69
0
6
Order By: Relevance
“…*P<0.05, **P<0.01, ***P<0.001 2013). Together with these previous observations and the recent finding that BP180-deficient epidermal keratinocytes display an abnormally high IL-8 response under various inflammatory stimuli (Van den Bergh et al 2012), our current results support the assumption that targeting BP180 directly affects the epidermal keratinocyte proinflammatory cytokine response (Schmidt et al 2000(Schmidt et al , 2001Messingham et al 2011;Van den Bergh et al 2012).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…*P<0.05, **P<0.01, ***P<0.001 2013). Together with these previous observations and the recent finding that BP180-deficient epidermal keratinocytes display an abnormally high IL-8 response under various inflammatory stimuli (Van den Bergh et al 2012), our current results support the assumption that targeting BP180 directly affects the epidermal keratinocyte proinflammatory cytokine response (Schmidt et al 2000(Schmidt et al , 2001Messingham et al 2011;Van den Bergh et al 2012).…”
Section: Discussionsupporting
confidence: 78%
“…Similar to previous experiments, which showed that IgG or IgE autoantibodies from BP patients stimulated Fc receptorindependent production of IL-6 and IL-8 in primary cultures of normal human epithelial keratinocytes (NHEK) (Schmidt et al 2000(Schmidt et al , 2001Messingham et al 2011), we also observed a significant BP IgG-induced secretion of both cytokines compared to normal IgG using the HaCaT cell line. Cytokine background levels that were seen in medium containing normal IgG and which have also been reported by previous investigators may reflect the culture conditions on a plastic surface (and not human dermis) or may result from unspecific stimuli produced by keratinocytes (Schmidt et al 2000(Schmidt et al , 2001.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…IgE autoantibodies for atopic dermatitis and bullous pemphigoid has been previously demonstrated (7,8). These IgE autoantibodies play important roles in each disease.…”
Section: Discussionmentioning
confidence: 96%